Characterization of deformed hatchlings of Octopus vulgaris obtained under captivity from a small female - Jiménez-Prada, Pablo (2018)
The common octopus (Octopus vulgaris), a promising species for aquaculture, spawns easily under cap-tivity from mature females (usually above 1 kg wet weight). Octopus juveniles and adults are collectedfrom nature to obtain eggs and paralarvae for aquaculture development trials. In July 2011, a very smallfemale (150 g wet weight but with an age estimation of 300 days-old) spawned almost 77,000 paralar-vae. Malformations of paralarvae were noticed in the first spawning days, namely the absence of arms.Despite not being lethal, these abnormalities might be derived from the physiological condition of thebreeding specimen (the female’s lower weight to the estimated amount of living days), which might beeventually related to nutritional unbalances or genetic parameters that were transferred to the eggs.